Variability and the control of rotation during springboard diving - Sinclair, P. J.; Walker, C. A.; Cobley, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This study explored the variability in angular velocity profiles across multiple somersault dives. Four international level divers performed 4-6 repeated dives of either 3½ somersaults with pike, or 4½ with tuck, from a 3 m springboard. An inertial measurement unit (IMU) was attached to the lower back to record angular velocity during all trials. Each diver produced highly consistent patterns of dive time duration and angular velocity, with standard deviations less than 1% of the mean. No consistent pattern of correlation between velocity and duration of the held tuck/pike position was apparent, and no other evidence of mid-dive feedback control was evident from the present methodology. This may be the result of performing dives with a high degree of difficulty, providing little time for movement adjustments during 'kick out' to affect water-entry.